DISTINCTIVE FEATURES OF DEVELOPING STUDENTS’ LINGUOCULTURAL COMPETENCE IN FOREIGN LANGUAGE TEACHING (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The article examines the role of linguocultural competence in the context of foreign language education, highlighting its essential place in fostering effective cross-cultural communication. The study explores the challenges and methodologies of integrating cultural and linguistic knowledge in language curricula, considering that linguistic elements alone are insufficient for true communicative competence.